Teacher identity and pedagogical content knowledge in grammar teaching among ESL primary school teachers - Ahmad, Norhakimah Khaiessa (2020)
This study explored how teachers who are engaged with young learners used selfconstructed metaphors to conceptualise their identity in grammar teaching. The examination of teacher identity was conducted through qualitative approach. Three experienced teachers were involved in this study. Employing a multiple case study design, data sources were collected from semi-structured interviews, stimulated recall interviews, lesson observations, observation field notes, and Picture Perfect (teaching metaphors reflected in the form of pictures). To answer each research question, data were analysed through coding, categorizing, and identifying sub-themes for the development of the main theme. The findings revealed that Teacher as Structural Builder emerged as the primary role in grammar teaching. The sub-identities of knowledge provider, chef, planner, diagnostician, and gem carver illustrated the participants planned, designed, and occasionally modified the grammar tasks to enhance children’s understanding and enable them to construct the structure of grammar items before they used it in written or spoken form. Teacher as Classroom Manager was the secondary role in grammar teaching. The sub-identities included the roles of manager, mother, and juggler, wherein teachers adopted these roles to manage both lessons and pupils in grammar lessons. These findings imply that identities were individually constructed on a moment-to-moment basis and evolved based on the pedagogical techniques and grammar tasks. All teachers practised balanced knowledge of learners and self. This outcome exhibits that the construction and negotiation of identities were accomplished by teacher-pupil interactions, classroom practices, personal language learning experience, and balanced knowledge of learners and self. This study benefits the stakeholders due to the pressing need for continuing professional development programme to cultivate self-understanding among in-service teachers in structuring their pedagogical reasoning and raising awareness of factors that may impede or facilitate identity development in grammar teaching. It is recommended that further examination on the primary and secondary role identities among teachers of young learners in grammar teaching is conducted in different types of primary school.